The Influence of Spatial Planning and Work Facilities on the Work Effectiveness of Radio Republic of Indonesia (RRI) Medan Employees - Miranda; Maidalena; Nur Ahmadi Bi Rahmani (Jurnal Manajemen Bisnis, 2024)
Finding out how office design and amenities affect productivity is the primary goal of this study. This study makes use of quantitative research methods. Questionnaires were used as a means of gathering information for this study. The data processing in this research was carried out using the SPSS 22 program, and the sample size was 30 respondents. Findings from the study's multiple linear regression analysis revealed that, while the spatial layout variable (x1) had no effect on RRI Medan employees' work effectiveness (-0.047), the facility variable work (x2) had a positive effect (0.494). Coefficient of determination (R square) findings show that spatial planning and work facilities affect work effectiveness by 0.618, or 61.8%, whereas other factors, not addressed in this study, impact it by 38.2%.